The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/08941939.2017.1284964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Indices and Red Cell Distribution Width as New Biomarkers for the Diagnosis of Acute Appendicitis

Abstract: Increased PDW combined with elevated WBC and neutrophil counts maybe used as diagnostic tests in the cases of acute appendicitis, while MPV and RDW levels were not useful diagnostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
63
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 49 publications
17
63
4
3
Order By: Relevance
“…Recently, Plt counts and Plt-related parameters (such as PBW, MPW) have become the focus of interest for various diseases. Some studies have shown that Plt counts decrease in AA (36). In our study, Plt counts were significantly lower in the AG than in the CG (p<0.03).…”
Section: The Demographic Results Of Groupssupporting
confidence: 45%
“…Recently, Plt counts and Plt-related parameters (such as PBW, MPW) have become the focus of interest for various diseases. Some studies have shown that Plt counts decrease in AA (36). In our study, Plt counts were significantly lower in the AG than in the CG (p<0.03).…”
Section: The Demographic Results Of Groupssupporting
confidence: 45%
“…PDW values were significantly higher in the patient group than in the control group. 23,24 There are studies which found similar results and opposite results with our study. [23][24][25] It is known that WBC values are frequently elevated in patients with acute appendicitis.…”
Section: Discussioncontrasting
confidence: 36%
“…23,24 There are studies which found similar results and opposite results with our study. [23][24][25] It is known that WBC values are frequently elevated in patients with acute appendicitis. 23,26 In our study, WBC count was significantly higher in the acute appendicitis group.…”
Section: Discussioncontrasting
confidence: 36%
See 2 more Smart Citations